2021
DOI: 10.3390/cells10030604
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profile in Plasma Extracellular Vesicles of Parkinson’s Disease and the Association with Cognitive Function

Abstract: Plasma extracellular vesicles (EVs) containing various molecules, including cytokines, can reflect the intracellular condition and participate in cell-to-cell signaling, thus emerging as biomarkers for Parkinson’s disease (PD). Inflammation may be a crucial risk factor for PD development and progression. The present study investigated the role of plasma EV cytokines as the biomarkers of PD. This cross-sectional study recruited 113 patients with PD, with mild to moderate stage disease, and 48 controls. Plasma E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, systemic inflammation leads to the impairment of the BBB, thus inducing the infiltration of immune cells into the brain and activating microglia-dependent neuroinflammation [ 25 , 56 ]. Studies have reported the presence of elevated proinflammatory cytokine levels in the serum and plasma extracellular vesicles of patients with PD [ 57 , 58 , 59 ]. In the present study, rifaximin treatment significantly altered GM and downregulated blood proinflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, systemic inflammation leads to the impairment of the BBB, thus inducing the infiltration of immune cells into the brain and activating microglia-dependent neuroinflammation [ 25 , 56 ]. Studies have reported the presence of elevated proinflammatory cytokine levels in the serum and plasma extracellular vesicles of patients with PD [ 57 , 58 , 59 ]. In the present study, rifaximin treatment significantly altered GM and downregulated blood proinflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation also contributed to an increase in the risk of PD [ 51 ]. PwP exhibited elevated blood cytokine levels in serum and plasma extracellular vesicles compared with healthy controls [ 52 , 53 ]. (Gut dysbiosis is a substantial risk factor of elevated systemic inflammation through the destruction of the intestinal epithelial membrane and the entrance of pathogens and toxins from the intestinal lumen into the systemic circulation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of other plasma exosomal proteins, as the prion protein, apolipoprotein J (APOJ), ApoA1, CR1 subcomponent, cytokines, insulin receptor substrate 1 and proteasome complex proteins and several immunologic‐associated EVs surface markers, were also capable to distinguish PD cases from controls, while no differences were found for neurofilament light chain or BDNF levels (Anastasi et al, 2021; Chan et al, 2021; Chou et al, 2020; Chung, Chan, et al, 2020; Chung, Huang, et al, 2020; Kitamura et al, 2018; Leng et al, 2020; Vacchi et al, 2020; Vacchi et al, 2021). It was likewise reported that the levels of plasma NDEVs were increased in PD when compared with Controls (Ohmichi et al, 2019).…”
Section: Evs and Clinical Research On Neurodegenerative Disordersmentioning
confidence: 99%